GE_GERICHTE C/14568/2015 vom 25. Januar 2019 - GE Cour de justice (2019)
MANDAT ; HONORAIRES ; CHÈQUE ; RÉPARTITION DES RISQUES ; COURS DE CONVERSION ; INTÉRÊT MORATOIRE | CO.69; CO.74.al2.let1; CO.84.al1; CO.102; CO.104.al1; CO.107.al2